Variasi Bahasa, Singkatan, dan Kesalahan Ejaan pada Fitur Market Place di Facebook - Hanifah Monika Sulistyowati; Andi Haris Prabawa; Yakub Nasucha; Laili i Etika Rahmawat (ESTETIK : Jurnal Bahasa Indonesia, 2020)
The purposes of this study were to answer the following questions: (1) What are the forms of language variations found on the market place feature on Facebook? (2) What are the forms of word abbreviations found on the market place features on Facebook? (3) What are spelling errors in the market place feature on Facebook? This study used a qualitative method referring to the analyses of screenshots and data records. The results of this study revealed the following: 1) There are three variations of language, including Indonesian and English language variations, Indonesian and Javanese variations, and the variations of Indonesian, English, and Javanese. 2) There are two types of word abbreviations, namely Indonesian abbreviations and English abbreviations. 3) There are four forms of spelling errors, including a) Erroneous use of capital letters, b) erroneous use of the in-front letter, c) Errors in writing periods (.) and commas (,), and d) Errors in quotation marks (". .. ") and abbreviations or apostrophes ('').